Methodology for determining climate change by analysis of impurity concentrations in the glacier - Curmei, M. D.; Makarenko, T. I.; Melnyk, V. I.; Klishevich, G. V. (Ukrainian Antarctic Journal, 2019)
The work contains the analysis of possible distributions of aerosol impurities through the glacier depth in those regions of Antarctica, where synoptic maps have shown stabilization of cyclones; and based on this analysis a methodology has been proposed for the determination of climatic parameter changes (average temperature and atmospheric precipitation amount) over a long time period. The main sources of the impurities in the glaciers of Antarctica are marine and continental aerosols, carried by meridional circulation of air masses. The annual concentration of chemical impurities, carried from both ocean and continent, and fallen on the glacier with rain or snow, is approximately the same over a long time period, if the glacier is located in a region of stable cyclonic activity. In this case, for the analysis, ice cores are taken continuously through the glacier depth. Linear sizes of all samples are similar. The quantity of annual layers in the sample is determined based on the age of the lower and upper levels in the glacier, from where the sample is taken. The thickness of the annual ice layer in the glacier is determined by the amount of fallen atmospheric precipitation and ablation processes. Consequently, all samples correspond to the periods of both equal and different durability. The quantity of annual layers in the sample (n) characterizes the amount of atmospheric precipitation of the corresponding period. Changes in the impurity concentrations from sample to sample are connected with the relative change in temperature of the corresponding periods. Then the two parameters, the number of annual layers, n, and the layer impurity content, C, have been determined experimentally in each sample. Based on these two parameters, a new technique has been proposed that allows determination of approximate temperature and precipitation changes over the time period, equal to the age of the studied glacier.